Pengaruh Aspek Etnisitas pada Corporate Identity Batik Komar : Studi Kasus Interior Showroom - Vidya Kharishma (JURNAL RUPA, 2016)
Ethnicity is an important aspect that influences the design concept of batik showroom in Indonesia. Element of ethnic in batik showroom is intended to increasing consumer knowledge of company's culture as well as providing strong image of the company (Corporate Identity). As a result, it will increase consumer willingness to buy the products and also merge the consumers and the company since they have the same interest in the culture. Corporate identity in batik showroom has a strong correlation with consumer behavior. The methods to observe its effect on the interior design were the psychology and cultural approaches. Consumer behaviour were observed and it is concluded that the influence of intangible and tangible of Javanese cultures really exist. The results display that ethnicity can affect all elements of interior design in batik showroom to introduce the corporate identity.